Plant caspase-like proteases in plant programmed cell death - Xu, Qixian (Landes Bioscience, 2009)
Programmed cell death (PCD) is a genetically-controlled disassembly of the cell. In animal systems, the central core execution switch for apoptotic PCD is the activation of caspases (Cysteine-containing Aspartate-specific proteases). Accumulating evidence in recent years suggests the existence of caspase-like activity in plants and its functional involvement in various types of plant PCD, although no functional homologs of animal caspases were identified in plant genome. In this mini-review, we will cover the recent results on the existence of plant caspase-like proteases and introduce major technologies used in detecting the activation of caspase-like proteases during plant PCD.